Interorganizational Networks at the Network Level: A Review of the Empirical Literature on Whole Networks - Provan, Keith G.; Fish, Amy; Sydow, Joerg (Journal of Management, 2007)
This article reviews and discusses the empirical literature on interorganizational networks at the network level of analysis, or what is sometimes referred to as “whole” networks. An overview of the distinction between egocentric and network-level research is first introduced. Then, a review of the modest literature on whole networks is undertaken, along with a summary table outlining the main findings based on a thorough literature search. Finally, the authors offer a discussion concerning what future directions might be taken by researchers hoping to expand this important, but understudied, topic.